Antagonistic Potential of Fluorescent Pseudomonads Colonizing Wheat Heads Against Mycotoxin Producing Alternaria and Fusaria - Müller, Thomas; Ruppel, Silke; Behrendt, Undine; Lentzsch, Peter; Müller, Marina E. H. (Frontiers in Microbiology, 2018)
Natural control of phytopathogenic microorganisms is assumed as a priority function of the commensal plant microbiota. Under field conditions, ears of winter wheat were colonised with high consistency and at a high density by fluorescent pseudomonads at the late milk/early dough stage. Isolates of these bacteria were evaluated for their potential to protect crops from phytopathogenic Alternaria and Fusarium fungi. They were checked in the dual culture test for their ability to inhibit the fungal growth in vitro. Alternaria responded species-specifically and more sensitively to bacterial antagonism than the strain-specific reacting fusaria. However, the bacterial antagonists were not evenly distributed in the field. A total of 110 randomly selected Pseudomonas isolates were screened for genes involved in the biosynthesis of antibiotics by means of real-time qPCR. The phlD gene, the key gene for 2,4- diacetylphloroglucinol production, was found in none of these isolates. At least one of the phz, pltB, and prnC genes, encoding the biosynthesis of phenazine-1-carboxylic acid, pyoluteorin and pyrrolnitrin, respectively, were detected in 81% of the isolates tested. However, the antagonistic effect found in the dual culture assay was not necessarily associated with the presence of these antibiotic genes. Wheat grains as natural substrate were inoculated with selected antagonistic Pseudomonas isolates and Alternaria and Fusarium strains, respectively. The fungal growth was only slightly delayed, but the mycotoxin production was significantly reduced in most of these approaches. In conclusion, the distribution of phytopathogenic fungi of the genera Alternaria and Fusarium in the field is unlikely to be inhibited by naturally occurring pseudomonads. However, pseudomonads can reduce the production of Alternaria and Fusarium mycotoxins in wheat grains and thus have the potential to improve the crop quality.